2021
DOI: 10.3390/polym13071074
|View full text |Cite
|
Sign up to set email alerts
|

Hypomyelinating Leukodystrophy 15 (HLD15)-Associated Mutation of EPRS1 Leads to Its Polymeric Aggregation in Rab7-Positive Vesicle Structures, Inhibiting Oligodendroglial Cell Morphological Differentiation

Abstract: Pelizaeus–Merzbacher disease (PMD), also known as hypomyelinating leukodystrophy 1 (HLD1), is an X-linked recessive disease affecting in the central nervous system (CNS). The gene responsible for HLD1 encodes proteolipid protein 1 (plp1), which is the major myelin structural protein produced by oligodendroglial cells (oligodendrocytes). HLD15 is an autosomal recessive disease affecting the glutamyl-prolyl-aminoacyl-tRNA synthetase 1 (eprs1) gene, whose product, the EPRS1 protein, is a bifunctional aminoacyl-tR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…To determine whether, similar to other HLD-related cellular phenotypes [ 18 , 19 , 20 , 21 , 22 ], the R140X mutant proteins of POLR3A form protein aggregates in cells, we transfected the plasmid encoding POLR3A harboring the R140X mutation or the wild type into FBD−102b cells. The transfected cell images showed that the wild type POLR3A proteins were distributed throughout the cytoplasm and slightly in nuclei ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine whether, similar to other HLD-related cellular phenotypes [ 18 , 19 , 20 , 21 , 22 ], the R140X mutant proteins of POLR3A form protein aggregates in cells, we transfected the plasmid encoding POLR3A harboring the R140X mutation or the wild type into FBD−102b cells. The transfected cell images showed that the wild type POLR3A proteins were distributed throughout the cytoplasm and slightly in nuclei ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Cells from the oligodendroglial FBD−102b cell line (a mouse brain oligodendroglial precursor cell line) were kindly provided by Dr. Y. Tomo-oka (Tokyo University of Science, Chiba, Japan; and Riken, Saitama, Japan). FBD−102b cells [ 18 , 19 , 20 , 21 , 22 ] were cultured on standard cell culture dishes (Greiner, Oberösterreich, Germany) in a culture medium consisting of DMEM/Nutrient Mixture F-12 (Nacalai Tesque, Kyoto, Japan) containing 10% heat-inactivated FBS (Thermo Fisher Scientific, Waltham, MA, USA) and PenStrep (Thermo Fisher Scientific) in 5% CO 2 at 37 °C. To induce differentiation, FBD−102b cells were cultured for 5 days in the same culture medium without FBS on cell culture dishes with advanced TC polymer surface modification (Greiner) in 5% CO 2 at 37 °C [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations